Synergy-Based Bilateral Port: A Universal Control Module for Tele-Manipulation Frameworks Using Asymmetric Master–Slave Systems - Brygo, Anais; Sarakoglou, Ioannis; Grioli, Giorgio; Tsagarakis, Nikos (Frontiers in Bioengineering and Biotechnology, 2017)
Endowing tele-manipulation frameworks with the capability to accommodate a variety of robotic hands is key to achieving high performances through permitting to flexibly interchange the end-effector according to the task considered. This requires the development of control policies that not only cope with asymmetric master-slave systems, but also whose high-level components are designed in a unified space in abstraction from the devices specifics. To address this dual challenge, a novel synergy port is developed that resolves the kinematic, sensing and actuation asymmetries of the considered system through generating motion and force feedback references in the hardware-independent hand postural synergy space. It builds upon the concept of the Cartesian-based synergy matrix, which is introduced as a tool mapping the fingertips Cartesian space to the directions oriented along the grasp principal components. To assess the effectiveness of the proposed approach, the synergy port has been integrated into the control system of a highly asymmetric tele-manipulation framework, in which the 3-finger hand exoskeleton HEXOTRAC is used as a master device to control the SoftHand, a robotic hand whose transmission system relies on a single motor to drive all joints along a soft synergistic path. The platform is further enriched with the vision-based motion capture system Optitrack to monitor the 6D trajectory of the user’s wrist, which is used to control the robotic arm on which the SoftHand is mounted. Experiments have been conducted with the humanoid robot COMAN and the KUKA LWR robotic manipulator. Results indicate that this bilateral interface is highly intuitive and allows users with no prior experience to reach, grasp and transport a variety of objects exhibiting very different shapes and impedances. In addition, the hardware and control solutions proved capable of accommodating users with different hand kinematics. Finally, the proposed control framework offers a universal, flexible and intuitive interface allowing for the performance of effective tele-manipulations.